The Utilization of Black â White Panchromatic Aerial Photograph for Mass Movement Study in Karang Kobar Areas, Banjarnegara, Centra Java - Hardjono, Imam; Mangoensoekardjo, Karmono; Sutikno, S (Universitas Muhammadiyah Surakarta, 1997)
This is the result of applied remote sensingÂ for geological study the mass wasting in Karangkobar, the district of Banjarnegara, Central Java. The study on the mass wasting use the remote sensing method, by interpreting the blackwhite panhromatic aerial photographs, on the scale 1 : 50,000. The study is aimed at 1) revealing the capacity of the aerial photograph in supporting the study the mass wasting that an be identified by the aerial photographs; 2) to find out the influence of the physical environment and land-use on the mass wasting processes. The study in performed by using the visual interpretation method of the scale 1 : 50,000 black-white panchromati aerial photograph taken in 1994, using mirror stereoscope. The outcome of the aerial photograph interpretation is varis the quality of data and information. The data of interpretation of aerial photograph and the varis outcome in the spot are further tested in terms of its accuracy, particularly in its reltion with the aerial photograph interpretation. The technique of data analysis of the physical environment and the mass wasting is descriptive â comparative. The result of the study shows that the 1 : 50,000 black-white panchromatic aerial photograph can be used to identify and study both the mass wasting and influence of the physical environment on the mass wasting processes. The degree of identifying the mass wasting based on the aerial photograph interpretation is 75%. Compared to the previous studies, the present study hows that the mass wasting can be identified more easily by means of the 1 : 50,000 black â white panchromatic aerial photograph. Identifying the distribution of mass wasting are: a) the geological element (rock, geological structure, and stratigraphy); b) geomorphological elements (landform and the forming processes); the water condition (surface water and groundwater); and landuse (type and distribution). White marl â claystone type is the physical environmentsal element that has the most type is the physical environmentsal element that has the most dominant influence on the occuring of mass wasting in Karangkobar area.